STIGMA DAN DISKRIMINASI PADA ANAK DENGAN HIV/AIDS: STIGMA AND DISCRIMINATION IN CHILD WITH HIV/AIDS - Putu Dian Prima Kusuma Dewi; Putu Sukma Megaputri; Ni Luh Made Krisna Dwipayanti (LPPM STIKes Buleleng, 2026)
Stigma and discrimination against children living with HIV/AIDS remain major challenges in HIV control, as they impact children’s mental health, adherence to antiretroviral therapy (ART), access to healthcare, and quality of life. Scientific evidence on this phenomenon needs to be synthesised to support the development of effective interventions. The aim is to identify and synthesise scientific evidence regarding the forms, impacts, associated factors, and strategies for addressing stigma and discrimination against children living with HIV/AIDS. This study is a systematic literature review that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted on PubMed, ScienceDirect, ProQuest, and Google Scholar using the keywords HIV, children, stigma, discrimination, and HIV/AIDS. Articles were selected based on inclusion and exclusion criteria, followed by data extraction and narrative synthesis. A total of six articles met the criteria and were analysed. The synthesis revealed that stigma against children living with HIV/AIDS comprises enacted stigma, anticipated stigma and internalised stigma. Stigma is associated with depression, anxiety, social isolation, low adherence to antiretroviral therapy (ART), delayed disclosure of HIV status, and limited access to healthcare services. Factors influencing stigma include community knowledge, family support, healthcare workers and the social environment. Interventions such as education, training for healthcare workers, contact-based approaches, and the strengthening of healthcare policies have the potential to reduce stigma and discrimination. Stigma and discrimination against children living with HIV/AIDS are multidimensional issues that require comprehensive interventions involving families, healthcare workers, communities, and policy-makers to improve quality of life, treatment adherence, and access to healthcare services.